Proceedings of a Workshop on Characterizing and Defining the Social and Economic Domains of Sustainable Diets - Comerford, Kevin; Arndt, Channing; Drewnowski, Adam; Ericksen, Polly J.; Griffin, Tim; Hendrickson, Mary; Ingram, John; Nicholls, Jill (MDPI, 2020)
Global challenges associated with a growing demand for food in the face of finite natural resources and climate change have prompted concerns about the sustainability of our current food systems. As formulated by the Food and Agriculture Organization, the four principal domains of sustainable diets are health, economics, society, and the environment. While emphasizing the environmental cost and health impacts of current diets, the research literature has virtually ignored the vital economic and social aspects of sustainability. Without these components, critical inputs for decision-making about global challenges related to climate change and a growing demand for food are missing. National Dairy Council convened experts in sociology, economics, human nutrition, food systems science, food security, environmental health, and sustainable agriculture for a one-day workshop to define the social and economic domains of sustainability in service of better characterizing food-based dietary guidance that is both healthy and sustainable. The consensus recommendations were to (1) select social and economic indicators to complement the existing environmental and health ones, (2) better define appropriate concepts, terms, and measures to foster discussion across scientific disciplines, (3) reframe the focus on sustainable diets towards the goal of “achieving healthy dietary patterns from sustainable food systems”, and (4) complement the four domains, and incorporate the notions of geography, time, and cross-cutting considerations into sustainability frameworks. This publication summarizes the presentations, discussions, and findings from the 2019 workshop, and aims to catalyze further action to advance sustainability research and practice in the context of food-based dietary guidance and the Sustainable Development Goals.